Pemberdayaan komunitas masyarakat melalui inovasi berkelanjutan: mengubah limbah tempurung kelapa menjadi solusi ekonomi dan lingkungan - Asfar, Andi Muhammad Irfan Taufan; Adiansyah, Romi; Nur, Syarif; Asfar, Andi Muhamad Iqbal Akbar; Nurannisa, Andi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
The management of coconut shell waste is often overlooked by rural communities, despite its significant economic and environmental potential when properly processed. This community service program aimed to empower the residents of Tanete Village, Cina District, through innovative processing of coconut shell waste into cococharcoal. The methods employed included socialization, intensive training, and mentoring. The community was trained to produce cococharcoal using techniques such as carbonization, grinding, binder mixing, compaction, and briquette drying. Evaluation was conducted through pretests and posttests to measure technical understanding and skills before and after the training. The results showed a significant improvement, with the average posttest score reaching 82.3, compared to a pretest average of 52.3. This program had a positive impact by enhancing the community’s skills in utilizing coconut waste, creating new economic opportunities, and reducing environmental pollution. Additionally, the cococharcoal innovation contributed to reducing the carbon footprint through the use of environmentally friendly alternative energy. The outcomes of this initiative not only promoted the development of a local economy based on village resources but also supported sustainable development goals, particularly in clean energy and climate action. With these promising results, the program has the potential to be replicated in other areas as a model of sustainable, local resource-based community empowerment.